2018
DOI: 10.1128/jvi.01720-17
|View full text |Cite
|
Sign up to set email alerts
|

GalNAc-Specific Soybean Lectin Inhibits HIV Infection of Macrophages through Induction of Antiviral Factors

Abstract: Although it has been shown that some mannose-binding lectins (MBLs) exhibit significant activity against HIV infection, little is known about whether -acetylgalactosamine (GalNAc)-binding lectins have the ability to inhibit HIV infection. Here, we demonstrate that a soybean-derived lectin (SBL) with GalNAc-binding affinity could potently suppress HIV infection of macrophages in a dose-dependent fashion. Unlike the MBLs, which block HIV only through binding to the glycosylated envelope proteins (gp120 and gp41)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The coupling reaction of the sugar on the AAV surface was first studied by dot blot analysis using soybean lectin which binds selectively to GalNAc residues 37 and the A20 antibody. The positive dots with the A20 antibody, which recognized the entire capsid, indicated that AAV2 remained intact after the coupling procedure with 4 , 5 or 8 and subsequent dialysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The coupling reaction of the sugar on the AAV surface was first studied by dot blot analysis using soybean lectin which binds selectively to GalNAc residues 37 and the A20 antibody. The positive dots with the A20 antibody, which recognized the entire capsid, indicated that AAV2 remained intact after the coupling procedure with 4 , 5 or 8 and subsequent dialysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Antiviral lectins interact with glycan structures added as post-translational modifications to the viral envelope proteins [ 34 , 36 ]. The anti-HIV activity has been reported for the mannose-binding lectins such as the lectin from banana (BanLec), microvirin from the cyanobacterium Microcystis aeruginosa , scytovirin from the cyanobacteria Scytonema varium , lectin from snowdrop (GNA), and lectin from the red alga Griffithsia sp.…”
Section: Discussionmentioning
confidence: 99%
“…(Griffithsin—GRFT). They have been proposed as antiviral microbicides in the prevention of HIV transmission [ 36 , 37 ]. Anti-influenza activity has been shown for some lectins, such as BanLec [ 38 ], cyanovirin-N [ 39 ], NICTABA ( Nicotiana tabacum agglutinin), and UDA ( Urtica dioica agglutinin) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, binding affinity is achieved by the multivalent nature of the protein and the resulting “glycocluster effect” in combination with the sugar density of the ligand. , The binding behavior of carbohydrate-binding proteins is of particular interest because cancer cells and other pathogens show alterations in the typical glycosylation patterns on the cell surface (glycocalyx). These abnormalities in the glycocalyx can be targeted by certain lectins, paving the way for lectin-based diagnostics and therapies. Furthermore, multiple lectins are known to interact with a number of viruses, making them promising targets for the treatment and prevention of viral infections. , Dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) and mannose-binding lectin (MBL) are the subjects of extensive research due to their key role in pathogen response after viral infections, including HIV. The tetrameric structure of DC-SIGN leads to great selectivity toward mannose- and/or fucose-containing glycopolymers . Furthermore, MBL was found to play an important role in the immunological defense by binding to numerous parasites, viruses, and bacteria, such as Neisseria meningitis, Ebola, and Influenza A. MBL is presenting different structural forms ranging from dimers to hexamers based on oligomers exhibiting three peptide chains with a carbohydrate-recognition domain, which binds to multiple sugars and glycopolymers with high affinities …”
Section: Introductionmentioning
confidence: 99%
“…5−8 Furthermore, multiple lectins are known to interact with a number of viruses, making them promising targets for the treatment and prevention of viral infections. 9,10 Dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) and mannose-binding lectin (MBL) are the subjects of extensive research due to their key role in pathogen response after viral infections, including HIV. 11−15 The tetrameric structure of DC-SIGN leads to great selectivity toward mannose-and/or fucose-containing glycopolymers.…”
Section: ■ Introductionmentioning
confidence: 99%